Time-loss injuries in Junior Olympic taekwondo athletes - Pieter, W.; Zemper, E. D. (Sports Exercise and Injury, 1997)
The purpose of this study was to assess the time-loss injuries in Junior Olympic taekwondo athletes. Data were collected at two national tournaments and one international meet. Injury data were collected by project staff and tournament medical personnel with simple check-off forms that describe the athlete and nature, site, circumstances and severity of the injury. Non-parametric procedures were used to determine the differences between boys and girls relative to total time-loss injury rate, body part injured within each gender, as well as estimated days lost. The boys (25.54/1000 athlete-exposures) sustained a lower total time-loss injury rate than the girls (29.91/1000 athlete-exposures) (P = 0.021). No other significant differences were found, although the head and neck ranked second in time-loss injuries in both boys (8.57/1000 athlete-exposures) and girls (9.10/1000 athlete-exposures). Source: Sports Exercise and Injury (1997) 3, 31-42